STUDI KELAYAKAN DAN EFISIENSI USAHA PENGASAPAN IKAN DENGAN ASAP CAIR LIMBAH PERTANIAN - Swastawati, Fronthea (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2011)
The objective of this research is to assess feasibility study of smoking fish bussines with liquid smoke agriculture waste as one of the alternative substitute to traditional smoking industries which have some weakneses in term of safety and enviromental. The Method used was description case study with questionnaire as instrument to obtain data. Estimation model of double regression analysis was applied to interpretate the results. The production liquid of smoked using agriculture waste were feasible values NPV of 108.461.057; IRR (%) = 33,29%; and PP = 2,8 year. Whereas Catfish, Skipjack, and Stingray smoked fish values of NPV = 63,35; IRR = 24,74; PP = 3,31; NPV = 54,31; IRR = 23,33; PP = 3,35; NPV = 45,07; IRR = 21,50; PP = 3,46 respectively. The production of liquid smoked agriculture waste and smoked fish using liquid smoked agriculture waste were as it produce feasible excellence, safety product and acceptable to consumers and also profitable. Break Event Point also could be reached in a short period of time.